Industrial evolution of India in recent times, 1860-1939 - Gadgil, D.R. (Delhi, 1972)
THE first edition of this work, published in 1924, presented a sketch of the economic history of India from the fifties of the last century to the beginning of the war in 1914. It was first written as a thesis for the degree of Master of Letters of Cambridge University and was printed, except for a few verbal alterations, almost in the same form as the thesis. This part of the work has not been revised subsequently and re presents the portion of the publication ending with Chapter 14, 'The Pre-War Period-Conclusion'. When, in 1929, a second edition was put forth a new chapter dealing with all aspects of economic history of the period after 1914 was added to the original work. At the time of the issue of the third edition in 1933 this chapter was revised to keep it abreast of the times. At the time of the publication of the fourth edition in 1942 the chapter dealing with the period after 1914 was not revised but a long preface bringing out the main features of developments during the thirties was included.
Keywords: Industry- history .